(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
Research was conducted to study the irrigation regimes of soybean varieties in areas protected from wind erosion by cover barriers in 2021-2023 on deflated barren soils of the "At the Level of Opportunity" farm in the Koson district of the Kashkadarya region.